Slavery in USA - Kolchin, Peter (My University, 1997)
Manuscript written about the slavery in the USA
13 pgs. Typescript, letter-sized, sepia-toned, fair condition.
Keywords: Slavery - United States; Ethnic groups - United States.; United States - Economic conditions